Acetylcholine receptor-inducing activity stimulates expression of the epsilon-subunit gene of the muscle acetylcholine receptor. - Martinou, J C (1991)
Motor neurons regulate the transcription of acetylcholine receptor subunit genes in postsynaptic muscle fibers both through muscle electrical activity produced by motor neuron acetylcholine release and by mechanisms independent of such transmitter release. Factors secreted by the motor neuron may mediate activity-independent regulation, including the postnatal switch from alpha 2 beta gamma delta (embryonic type) to alpha 2 beta epsilon delta (adult type) receptors. We have investigated the effect of putative trophic factors, agents affecting second-messenger systems, and muscle activity on the levels of acetylcholine receptor subunit mRNAs in primary mouse muscle cultures. We found that ARIA (acetylcholine receptor-inducing activity), a 42-kDa glycoprotein purified on the basis of its ability to increase the synthesis of acetylcholine receptors in chick myotubes, increases epsilon-subunit mRNA levels up to 10-fold. In addition, ARIA stimulated alpha-, gamma-, and delta-subunit mRNA levels 2-fold but had no effect on the expression of the beta-subunit gene. These effects of ARIA were independent of muscle activity, and they were not mimicked by calcitonin gene-related peptide nor by thyroxine, forskolin, phorbol 12-myristate 13-acetate, the calcium ionophore A23187, basic fibroblast growth factor, or transforming growth factor beta. Based on these data, we suggest that ARIA may act at the mammalian neuromuscular junction to induce adult-type acetylcholine receptors.